Analisis Persediaan Bahan Baku Kertas Guna Meningkatkan Efesiensi Pengelolahan Persediaan pada Percetakan Wahyu Abadi : (Studi Kasus: UD. Wahyu Abadi Surabaya) - Agung Efendi, Muhammad; Purnama, Jaka (SURYA TEKNIKA, 2024)
Wahyu Abadi is a printing business located in Petemon, Surabaya. This company is capable of producing between 800-1,200 prints per day or equivalent to 50-70 reams of paper. In its operations, UD. Wahyu Abadi uses three types of paper raw materials: Art Paper, HVS, and NRC. Previously, the company made raw material purchases based on its own policies without using optimal inventory control methods. A study revealed that by implementing the Economic Order Quantity (EOQ) method, the company can optimize its raw material inventory costs. The most profitable purchase quantity for Art Paper is 12 reams with a 13order frequency within 6 months, saving inventory costs of Rp. 42,029 compared to the previous policy. For HVS paper, the optimal purchase quantity is 178 reams with an 18 order frequency within 12 months, saving inventory costs of Rp. 380,896. Meanwhile, for NRC paper, the optimal purchase quantity is 853 reams with an 18 order frequency within 12 months, saving inventory costs of Rp. 379,715. Additionally, the EOQ method also requires the company to provide safety stock and set a reorder point to anticipate delays in raw material delivery. This study recommends UD. Wahyu Abadi to implement the EOQ method in its raw material inventory management to improve cost efficiency.